Synthesis of anisotropic silica colloids. Issue 60 (28th July 2017) - Yu, Qiyu; Wang, Kun; Zhang, Jing; Liu, Mingyang; Liu, Yuanyuan; Cheng, Chao
Abstract : Morphological evolution of tadpole-like hollow silica particles, and corresponding TEM images of typical intermediate and final products. Abstract : A water-in-alcohol emulsion strategy was exploited for the preparation of various anisotropic silica colloids. Sodium citrate and highly concentrated polyvinylpyrrolidone (in the water-rich emulsion droplets) were utilized to costabilize the emulsion system. Simply by choosing proper alcohols and/or the mixing ratios of the alcohol mixtures, a wide range of shape- and structure-selective silica micro-/nanostructures, including hollow structures, were prepared. Some binary alcohol combinations, e.g. 1-heptanol/ethanol, can provide superb versatility via tuning the mixing ratio. In particular, the formation process of the anisotropic silica particles was examined. Tentatively, a "salting-out" mechanism was proposed to explain the formation of a Janus-like silica-droplet structure at the initial silica condensation stage, which is essential for the present anisotropic growth mode. The effect of the interfacial tensions between silica and the emulsion system was discussed. Interestingly, one-end-opened hollow structures, e.g. silica "tubes", can be achieved by arresting the anisotropic growth of hollow silica particles midway.